Epistemologi Islam Vis-À-Vis Teori Demarkasi Ilmu: Satu Penelitian Awal - Wan Mohd Fazrul Azdi Wan Razali (Universiti Sains Islam Malaysia, 2024)
The revelation is a credible source of knowledge, because it is imbued with knowledge that is interdisciplinary, as it also provides guidance to how the knowledge should be identified and comprehended. The Islamic Epistemology consists of explanations and guidance needed to guide mankind in their quest for civilization, through the breakthroughs of new findings and practices. However, during the Western post-Enlightenment period, the Demarcation of Knowledge Theory was introduced and later immersed into the Westernization of Knowledge and disseminated to the global communities. This journal article discusses various issues pertaining to this theory, that Muslims should be aware of and provides suggestions as to how the Islamic Epistemology could be empowered.